2016
DOI: 10.1002/qj.2900
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and coherence of mesoscale wind speeds over the sea

Abstract: A large offshore observational dataset from stations across the North and Baltic Seas is used to investigate the planetary boundary-layer wind characteristics and their coherence, correlation and power spectra. The data from thirteen sites, with pairs of sites at horizontal distances of 4 to 848 km, are analyzed for typical wind turbine nacelle heights. Mean wind characteristics, correlation and coherence are also calculated for analogous wind data from simulations with the Weather Research and Forecasting (WR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 33 publications
3
23
1
Order By: Relevance
“…sensor (the lowest height included in this analysis) have the lowest coherence values (and highest decay rate). The vertical coherence functions from Perdigão towers decay to their minimum value at a reduced frequency of ∼ 0.3, which is similar to the value of 0.36 calculated for wind over water (Mehrens et al, 2016). Coherence functions derived using wind speeds from ZephIR lidar z423 show slightly larger C values that are derived from sonic anemometer data from the nearby Tower 25 and exhibit high C values between measurements at 60 m a.g.l.…”
Section: Spectra and Coherencessupporting
confidence: 72%
See 3 more Smart Citations
“…sensor (the lowest height included in this analysis) have the lowest coherence values (and highest decay rate). The vertical coherence functions from Perdigão towers decay to their minimum value at a reduced frequency of ∼ 0.3, which is similar to the value of 0.36 calculated for wind over water (Mehrens et al, 2016). Coherence functions derived using wind speeds from ZephIR lidar z423 show slightly larger C values that are derived from sonic anemometer data from the nearby Tower 25 and exhibit high C values between measurements at 60 m a.g.l.…”
Section: Spectra and Coherencessupporting
confidence: 72%
“…The decay of coherence functions for vertical displacements is in the range found in flat terrain (Solari, 1987;Vigueras-Rodríguez et al, 2012). However, coherences for the large horizontal displacements (> 700 m) among towers do not fully conform to an exponential fit (as with those presented in Mehrens et al, 2016) and are characterized by smaller decay coefficients than have been found in research conducted in less complex terrain.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…2013). We refer to these papers for details beyond the short overview provided coherence of various velocity components in tower micrometeorological data (Davenport, 1961a;Panofsky and Singer, 1965;Pielke and Panofsky, 1971;Naito and Kondo, 1974;Panofsky et al, 1974;Brook, 1975;Seginer and Mulhearn, 1978;Kanda and Royles, 1978;Soucy et al, 1982;Bowen et al, 1983;Saranyasoontorn et al, 2004), investigations including the lateral/spanwise coherence (Kristensen and Jensen, 1979;Ropelewski et al, 1973;Panofsky and Mizuno, 1975;Perry et al, 1978;Kristensen, 1979;Kristensen et al, 1981;Schlez and Infield, 1998), the coherence of temperature fluctuations (Davison, 1976) and even meso-scale applications (typically in the horizontal directions) (Hanna and Chang, 1992;Woods et al, 2011;Vincent et al, 2013;Larsén et al, 2013;Mehrens et al, 2016). Together, these measurements cover a great variety of terrain and topography.…”
Section: Comparing Davenport's Hypothesis Tomentioning
confidence: 99%